Mediation Challenges in Civil Dispute Resolution: A Case Study of Civil Case Number 72/Pdt.Plg/2023 at the Palembang District Court - Riyadi , Bambang Sugeng; Holijah, Holijah; Tanzili, Mulyadi (Jurnal Ilmu Hukum Kyadiren, 2025)
As a country governed by the rule of law, Indonesia upholds the principle of legal supremacy, requiring both citizens and government officials to comply with applicable laws. This study examines the resolution of civil cases through mediation, focusing on Civil Case Number 72/Pdt.Plg/2023 at the Class 1A Palembang District Court, and analyzes the factors influencing the plaintiff’s and defendant’s decisions to accept or reject mediation. This research employs a normative method with a qualitative approach, relying on secondary data. The findings indicate that, despite an initial willingness to resolve the dispute amicably, challenges such as differences in family perspectives and a lack of understanding of the mediation process hindered its success. Consequently, the plaintiff withdrew the lawsuit, and the case was ultimately resolved through litigation, resulting in a court ruling granting all claims, including immaterial compensation of IDR 100,000,000. Several factors influenced the parties’ decisions, including legal considerations, the role of judges and mediators, infrastructure limitations, community attitudes, and the prevailing legal culture.